A Critical Geographic Approach to Youth Civic Engagement: Reframing Educational Opportunity Zones and the Use of Public Spaces. (February 2016) - Burke, Kevin J.; Greene, Stuart; McKenna, Maria K.
The article draws on work in Critical Geography Studies and Photovoice methodology, to illustrate the ways in which youth in an inner city conceptualize neighborhoods and public spaces. We utilize youth's photographs, narratives, and maps to tell a story of youth's lived experiences and argue that these experiences are vital sources of knowledge about how an unequal distribution of resources affects them. It is important, we argue, to not only hear student voices but also prepare them to become critical, independent thinkers, who can use multiple literacies as affordances for creating changes that help nourish them. This means fundamentally rethinking how as educators we listen to and walk with youth as they reframe the ways in which we might use public parks, neighborhood schools, community centers, and sidewalks as pedagogical and political spaces.